PENGARUH KUALITAS PRODUK, BRAND AWARENESS TERHADAP BRAND LOYALTY MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA USAHA SABLON SP SPORTWEAR KOTA TULUNGAGUNG - Fadhil Alfito; Bambang Suwarsono; Brahma Wahyu Kurniawan (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to test and explain the influence of product quality, brand awareness to brand loyalty through purchasing decisions as an interverning variable in the Sablon Sp Sportwear in Tulungagung City. This research uses quantitative methods and the population studied is consumers who have screen printed or purchased t-shirts more than once at SP Sportwear Tulungagung, totaling 122 people from January to February 2024. The number of samples taken was 93 respondents, and the sampling method used non probability sampling with technique purposive sampling. Data collected through questionnaires, while analysis techniques use validity tests, realism tests, R tests Square, and test the hypothesis. The research results show that (1) there is a positive but not significant influence between Product Quality and Brand Loyalty with a t statistics value of 1.600 which is smaller than the t value of 1.97, and a P-Values ​​= 0.113 which is greater than α = 0.05, (2) there is a positive and significant influence between Brand Awareness to Brand Loyalty with a t statistics value of 0.640 which is smaller than the t value of 1.97, and a P-Values ​​value = 0.000 which is smaller than α = 0.05, (3) there is a positive and significant influence between Purchasing Decisions on Brand Loyalty with a t statistics value of 31.851 which is greater than the t value of 1.97, and a P-Values ​​value = 0.000 which is smaller than α = 0.05, (4) there is a positive but not significant influence between Product Quality on Purchasing Decisions with a t statistics value of 2.208 which is greater than the t value of 1.97, and a P-Values ​​value = 0.113 which is greater than α = 0.05, (5) there is a positive and significant influence between Brand Awareness on Purchasing Decisions with a t statistics value of 31.851 which is greater than the t value of 1.97, and a P-Values ​​value = 0.000 which is smaller than α = 0.05, (6) there is a significant influence on Purchasing Decisions which is able to mediate Product Quality on Brand Loyalty with a t statistics value of 2.223 which is greater than the t value of 1.97, and a P-Values ​​value = 0.028 which is smaller than α = 0.05, (7) there is a significant influence on purchasing decisions that is able to mediate Brand Awareness to Brand Loyalty with a t statistics value of 5.124 which is greater than the t value of 1.97, and a P-Values ​​value = 0.000 which is smaller than α = 0.05.